Diaphragm assembly, battery cell, battery and electric device

By using an inorganic material coating with a volume average particle size less than 0.16 μm in the separator assembly of the battery cell, the problem of high short circuit risk during charging and discharging of the battery cell is solved, and the effect of reducing the short circuit risk without reducing the rate performance is achieved.

CN119905777APending Publication Date: 2025-04-29CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202311407537.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing battery cells are prone to short circuits during charging and discharging, and it is difficult to reduce the risk of short circuit without reducing the rate performance.

Method used

A diaphragm assembly is provided, including a first diaphragm, which consists of a first base film and a first coating, which is located on at least one side surface of the first base film and contains an inorganic material with a volume average particle size Dv50≤0.16 μm. Through this design, the diaphragm assembly is denser, reducing the risk of dendrites penetration.

Benefits of technology

Without deteriorating the rate performance of the battery cell, the risk of short-circuiting of the battery cell is reduced and the overall performance of the battery cell is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905777A_ABST
    Figure CN119905777A_ABST
Patent Text Reader

Abstract

The invention discloses a diaphragm assembly, a battery monomer, a battery and an electric device, and belongs to the technical field of batteries. The diaphragm assembly comprises a first diaphragm, the first diaphragm comprises a first base membrane and a first coating, the first coating is located on the surface of at least one side of the first base membrane, the first coating comprises an inorganic material, and the volume average particle size Dv50 of the inorganic material meets the condition that Dv50 is smaller than or equal to 0.16 [mu] m. According to the technical scheme provided by the embodiment of the invention, the risk of short circuit of the battery monomer can be reduced under the condition that the rate capability of the battery monomer is not deteriorated, so that the battery monomer has relatively good comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a diaphragm assembly, a battery cell, a battery and an electrical device. Background Art

[0002] As environmental pollution becomes increasingly serious, the new energy industry has attracted more and more attention. In the new energy industry, battery technology is an important factor related to its development.

[0003] A battery cell includes a positive electrode sheet, a negative electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet. The arrangement of the separator is crucial to the performance of the battery cell. Therefore, how to provide a separator assembly to improve the comprehensive performance of the battery cell is a technical problem that needs to be solved urgently. Summary of the invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a diaphragm assembly to reduce the short circuit risk of the battery cell without deteriorating the rate performance of the battery cell, thereby improving the comprehensive performance of the battery cell.

[0005] In order to achieve the above-mentioned objectives, the present application provides a diaphragm assembly, a battery cell, a battery and an electrical device.

[0006] In a first aspect, a diaphragm assembly is provided, comprising: a first diaphragm, wherein the first diaphragm comprises a first base film and a first coating, the first coating is located on the surface of at least one side of the first base film, the first coating comprises an inorganic material, and the volume average particle size Dv50 of the inorganic material satisfies: Dv50≤0.16μm.

[0007] The embodiment of the present application provides a diaphragm assembly, which includes a first diaphragm, and the first diaphragm includes a first base film and a first coating located on at least one side of the first base film. The volume average particle size Dv50 of the inorganic material in the first coating satisfies: Dv50≤0.16μm. In this way, the inorganic material has a smaller particle size, and the size of the gaps between the inorganic materials is smaller, which is more conducive to blocking the passage of dendrites, so that the diaphragm assembly is denser, the risk of being punctured by dendrites is reduced, and the risk of short circuit in the battery cell is reduced. In addition, the diaphragm assembly is denser, and the requirements for the thickness of the diaphragm assembly are correspondingly reduced. The diaphragm assembly can achieve the effect of blocking dendrites from piercing the diaphragm assembly when the thickness remains unchanged or even decreases, thereby reducing the impact of the thickness of the diaphragm assembly on the rate performance of the battery cell. Therefore, the technical solution of the embodiment of the present application can reduce the risk of short circuit in the battery cell without deteriorating the rate performance of the battery cell, which is conducive to improving the comprehensive performance of the battery cell.

[0008] In a possible implementation, the volume average particle size Dv50 of the inorganic material satisfies: 0.04 μm ≤ Dv50 ≤ 0.16 μm. In this way, the inorganic material has a more appropriate volume average particle size, which can reduce the risk of gelation of the prepared slurry due to the small volume average particle size of the inorganic material.

[0009] In a possible implementation, the porosity σ1 of the first base film satisfies: 30%≤σ1≤45%.

[0010] In the above technical solution, the porosity of the first base film is relatively small, and the first base film is also relatively dense, so that the diaphragm assembly is relatively dense, and the risk of the diaphragm assembly being punctured is reduced. In addition, during the charge and discharge process of the battery cell, it is not easy to precipitate metal (such as lithium or sodium) on the surface of the first coating layer, and the surface of the first coating layer is relatively flat. When the first coating layer is arranged toward the negative electrode plate, it is beneficial to further reduce the short circuit risk of the battery cell.

[0011] In a possible implementation, the diaphragm assembly further includes: a second diaphragm, the second diaphragm is located on a side of the first coating layer away from the first base film, and the porosity of the second diaphragm is greater than the porosity of the first diaphragm. The porosity of the second diaphragm is relatively large, and the porosity of the first diaphragm is relatively low, so that in the diaphragm assembly, the size of the voids can form a gradient distribution, and the overall porosity of the diaphragm assembly is increased, which is conducive to improving the liquid retention capacity of the diaphragm assembly while having the effect of preventing dendrite puncture.

[0012] In a possible implementation manner, the second diaphragm includes: a second base film, and the second base film is located on a side of the first coating layer away from the first base film.

[0013] In a possible implementation, the second diaphragm includes: a second base film and a second coating, wherein the second coating is located between the second base film and the first coating; or the second base film is located between the second coating and the first coating.

[0014] In the above technical solution, the size of the gaps in the diaphragm assembly can form a gradient distribution, and the liquid retention capacity of the diaphragm assembly is improved.

[0015] In a possible implementation, the number B of voids on the surface of the first coating in an area of ​​200 nm×200 nm satisfies: 10≤B≤60.

[0016] In the above technical solution, by reasonably setting the range of B, the diaphragm assembly is denser and the strength against dendrite penetration is increased; at the same time, the number of voids will not be too many, so that the particle size of the inorganic material will not be too small, which can reduce the risk of gelation of the slurry of the first coating during the preparation of the slurry of the first coating.

[0017] In a possible implementation, in the first coating layer, the size C of the gaps between the inorganic materials satisfies: C≤50nm; optionally, C≤20nm. In this way, the first coating layer is denser and the risk of the diaphragm assembly being punctured is lower.

[0018] In a possible implementation, the inorganic material includes a ceramic material; optionally, the inorganic material includes at least one of silicon dioxide, aluminum oxide, zirconium oxide or boehmite. The above inorganic materials are used to facilitate the preparation of a relatively dense first coating.

[0019] In a possible implementation, the surface density D of the first coating satisfies: D≤3g / mm 2 ; Optionally, D≤2.5g / mm 2 In this way, the first coating layer has a smaller surface density, so that the first coating layer can have a smaller thickness.

[0020] In a possible implementation, the thickness d1 of the first coating satisfies: 1.5 μm ≤ d1 ≤ 4 μm; optionally, d1 satisfies: 1.5 μm ≤ d1 ≤ 2 μm. In this way, the first coating has a smaller thickness and a higher degree of densification, so that the battery cell can have better rate performance with a lower short circuit risk.

[0021] In a possible implementation, the porosity σ0 of the diaphragm assembly satisfies: 30%≤σ0≤40%. In this way, the porosity of the diaphragm assembly is lower, the diaphragm assembly is denser, the risk of being punctured by dendrites is lower, and the risk of short circuit of the battery cell is lower.

[0022] In a second aspect, a battery cell is provided, comprising the diaphragm assembly in the first aspect and any possible implementation thereof.

[0023] In a possible implementation, the battery cell further includes: a positive electrode sheet and a negative electrode sheet, the diaphragm assembly is disposed between the positive electrode sheet and the negative electrode sheet, and the first coating faces the negative electrode sheet. In this way, the negative electrode sheet faces the side of the diaphragm assembly where the first coating is disposed, thereby facilitating better protection of the diaphragm assembly.

[0024] In a possible implementation, the battery cell is an alkali metal battery cell; optionally, the battery cell is a sodium metal battery cell. Alkali metal battery cells are prone to forming dendrites on the negative electrode during the charge and discharge process. By providing the diaphragm assembly in the above embodiment in the alkali metal battery cell, the risk of internal short circuit of the battery cell is reduced, and the battery cell has better rate performance.

[0025] In one possible implementation, the battery cell is a sodium ion battery cell or a lithium ion battery cell. In the case of sodium precipitation in a sodium ion battery cell or lithium precipitation in a lithium ion battery cell, the diaphragm assembly is relatively dense, so the risk of being punctured by the precipitated lithium dendrites or sodium dendrites is low. In addition, the sodium ion battery cell or the lithium ion battery cell can also be a battery cell with a smaller CB value.

[0026] In a possible implementation, the battery cell is a secondary battery cell.

[0027] In a third aspect, a battery is provided, comprising the battery cell in the second aspect and any possible implementation thereof.

[0028] In a fourth aspect, an electrical device is provided, comprising the battery described in the third aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0030] Figure 1 A schematic diagram of a diaphragm assembly according to an embodiment of the present application;

[0031] Figure 2 A schematic diagram of a diaphragm assembly according to an embodiment of the present application;

[0032] Figure 3 A schematic diagram of a diaphragm assembly according to an embodiment of the present application;

[0033] Figure 4 A schematic diagram of a diaphragm assembly according to an embodiment of the present application;

[0034] Figure 5 A schematic diagram of a diaphragm assembly according to an embodiment of the present application;

[0035] Figure 6 A schematic diagram of a diaphragm assembly according to an embodiment of the present application;

[0036] Figure 7 A schematic diagram of a diaphragm assembly according to an embodiment of the present application;

[0037] Figure 8 A schematic diagram of a battery cell according to an embodiment of the present application;

[0038] Fig. 9 A schematic diagram of a battery according to an embodiment of the present application;

[0039] Fig.10 FIG. 1 is a schematic diagram of an electrical device according to an embodiment of the present application. DETAILED DESCRIPTION

[0040] Below, the embodiments of the diaphragm assembly, battery cell, battery, and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0041] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0042] If there is no special description, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. If there is no special description, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0043] As environmental pollution becomes increasingly serious, the new energy industry has attracted more and more attention. In the new energy industry, battery technology is an important factor related to its development. The battery cell includes a positive electrode sheet, a negative electrode sheet and a diaphragm located between the positive electrode sheet and the negative electrode sheet. The setting of the diaphragm is crucial to the performance of the battery cell. The diaphragm may include a separate base film, or a base film and a ceramic coating provided on the surface of the base film. During the charge and discharge process of the battery cell, metal dendrites may precipitate on the surface of the negative electrode sheet. The diaphragm can block the metal dendrites to a certain extent, reducing the risk of metal dendrites piercing the diaphragm, causing the positive electrode sheet and the negative electrode sheet to overlap, resulting in a battery short circuit.

[0044] However, for metal battery cells, the probability of dendrites is high, and a single base film or a conventional ceramic coating only on the base film is difficult to achieve a good anti-dendrite puncture effect. Increasing the thickness of the ceramic coating can improve the puncture resistance of the diaphragm, but the thickness of the ceramic coating increases, resulting in an increase in the overall thickness of the diaphragm, making the ion transmission path more tortuous or longer, which will lead to a decrease in rate performance and other performance.

[0045] In view of this, the present application provides a diaphragm assembly, which, by setting the particle size of the material in the coating of the diaphragm assembly, enables the diaphragm assembly to have better anti-dendrite puncture ability and a suitable ion transmission path, so that the battery cell has a lower short circuit risk without deteriorating the rate performance.

[0046] [Diaphragm assembly]

[0047] Figure 1 is a schematic diagram of a diaphragm assembly according to an embodiment of the present application, Figure 2 Schematic diagram of a diaphragm assembly according to an embodiment of the present application. Figure 1 and Figure 2 As shown, the diaphragm assembly 1 includes: a first diaphragm 11.

[0048] The first diaphragm 11 includes a first base film 111 and a first coating layer 112 . The first coating layer 112 is located on at least one surface of the first base film 111 .

[0049] The first base film 111 has two opposite surfaces along the thickness direction of the first base film 111. The thickness direction of the first base film 111 can be Figure 1 The z direction in .

[0050] For example, Figure 1 As shown, the first coating layer 112 may be located on a surface on one side in the thickness direction of the first base film 111. In other arrangements, the first coating layer 112 may also be located on surfaces on both sides in the thickness direction of the first base film 111, that is, the first coating layer 112 is provided on both opposite surfaces in the thickness direction of the first base film 11.

[0051] The first coating layer 112 includes an inorganic material, and the volume average particle size Dv50 of the inorganic material satisfies: Dv50≤0.16 μm.

[0052] The inorganic material may include a ceramic material, for example, the inorganic material is aluminum oxide.

[0053] The volume average particle size Dv50 of the inorganic material may be 0.02 μm, 0.04 μm, 0.08 μm, 0.1 μm, 0.16 μm, or any value within the above range.

[0054] The inorganic material has a smaller volume average particle size, so the size of the gaps between the particles of the inorganic material is smaller, the probability of dendrite growth encountering obstacles is increased, and the dendrites are not easy to pass through the small gaps, so that the first coating 112 is relatively dense, which can effectively reduce the risk of the diaphragm assembly 1 being punctured, thereby reducing the risk of short circuit in the battery cell.

[0055] Compared with inorganic materials with larger particle sizes, such as inorganic material particles with a volume average particle size greater than 1 μm, the size of the gaps between the inorganic material particles in this embodiment is smaller, the number of gaps increases, and the path for metal ions to pass through is more tortuous. However, the first coating 112 prepared from the inorganic material of this embodiment has a higher density, so that the first coating 112 has a higher ability to prevent dendrite puncture with a smaller thickness, so that the technical solution of this embodiment can take into account the density of the diaphragm assembly 1 and the transmission path of ions, thereby reducing the impact of the thickness of the diaphragm assembly on the rate performance of the battery cell.

[0056] It should be noted that the diaphragm assembly 1 may include only the first diaphragm 11 , or may include a diaphragm structure other than the first diaphragm 11 .

[0057] In this embodiment, the porosity of the first base film 111 is not particularly limited as long as the first coating layer 112 satisfies the above settings.

[0058] In the embodiment of the present application, the inorganic material has a smaller particle size, the size of the gaps between the inorganic materials is smaller, and the first coating 112 is denser. In addition, by setting the particle size of the inorganic material to meet the above range, the first coating 112 can have a higher degree of densification when the thickness is small, which is beneficial to reduce the length of the ion transmission path. Therefore, the technical solution of the embodiment of the present application can take into account the density of the diaphragm assembly 1 and the transmission path of the ions, so that the short circuit risk of the battery cell is low, and the battery cell also has a higher rate performance, which is beneficial to improve the performance of the battery cell.

[0059] In some embodiments, the volume average particle size Dv50 of the inorganic material satisfies: 0.04 μm≤Dv50≤0.16 μm.

[0060] Compared with inorganic materials with smaller particle sizes, for example, inorganic materials with a volume average particle size of less than 0.04 μm, the risk of inorganic material agglomeration and slurry gelation due to the small particle size of the inorganic material can be reduced during the process of preparing slurry using the inorganic material of this embodiment.

[0061] In some embodiments, the porosity σ1 of the first base film 111 satisfies: 30%≤σ1≤45%. σ1 may be 30%, 40%, 45%, or any value within the above range.

[0062] As an example, σ1 is 40%.

[0063] As another example, σ1 is 30%. In this way, the porosity of the first base film 111 is lower, so that the first diaphragm 11 has a stronger ability to prevent dendrites from piercing.

[0064] In this embodiment, combined with Figure 2 As shown, the porosity σ1 of the first base film 111 satisfies: 30%≤σ1≤45%, and the volume average particle size of the inorganic material in the first coating 112 satisfies Dv50≤0.16μm. In this way, the diaphragm assembly 1 is denser, and the risk of being punctured by dendrites is further reduced. In addition, during the charge and discharge process of the battery cell, it is not easy to generate metal dendrites (such as lithium or sodium precipitation) on the surface of the first coating 112, and the surface of the first coating 112 is relatively flat; and when the first coating 112 is arranged toward the negative electrode plate (that is, when the first coating 112 is in direct contact with the negative electrode plate), it is beneficial to further reduce the short circuit risk of the battery cell.

[0065] In addition, compared with the material with a volume average particle size greater than 0.16 μm, the particle size of the inorganic material of this embodiment is smaller, so the ratio of the protruding height of the inorganic material particles to the height of the first coating 112 is smaller, so that the surface of the first coating 121 of this embodiment is smoother and has a lower roughness. The protruding degree of the inorganic material particles can be observed by an atomic force microscope (AFM), and the microscopic morphology observed by the AFM can be characterized.

[0066] Figure 3 Schematic diagram of a diaphragm assembly according to an embodiment of the present application. Figure 2 ,exist Figure 3 In the experiment, the particle size of inorganic materials is larger and the gaps between inorganic materials are also larger.

[0067] In some embodiments, reference Figure 3As shown, the diaphragm assembly 1 includes a first diaphragm 11, and the first diaphragm 11 includes a first base film 111 and a first coating 112, and the porosity σ1 of the first base film 111 satisfies: 30%≤σ1≤45%. σ1 can be 30%, 40%, 45% or any value within the above range. In this embodiment, the particle size of the inorganic material in the first coating 112 is not particularly limited, but the porosity of the first base film 111 is limited. Compared with a base film with a porosity of 45%-55%, the porosity of the first base film 111 is smaller, and the first base film 111 is denser, so that the performance of the diaphragm assembly 1 against dendrite penetration is increased.

[0068] It should be noted that Figure 2 and Figure 3 It is used to explain the gaps in the diaphragm assembly 1, the gaps between inorganic material particles, and the size of inorganic material particles. In addition, it can also explain the gaps between particles of the first base film 111 (the particle refers to the smallest unit constituting the first base film 111) to reflect the gap size of the first base film 111 and the gap size of the first coating 112.

[0069] Figure 4 This is a schematic diagram of a diaphragm assembly according to an embodiment of the present application. Figure 4 As shown, the diaphragm assembly 1 further includes: a second diaphragm 12 .

[0070] The second diaphragm 12 is located on a side of the first coating layer 112 away from the first base film 111 , that is, the first coating layer 112 is located between the second diaphragm 12 and the first base film 111 .

[0071] The porosity of the second diaphragm 12 is greater than that of the first diaphragm 11. In this way, the size of the voids in the second diaphragm 12 is larger, and the size of the voids in the first diaphragm 11 is smaller, so that a gap with a gradient distribution can be formed between the first diaphragm 11 and the second diaphragm 12, and a certain amount of electrolyte can be stored in the large gap, which is beneficial to improving the liquid retention capacity of the diaphragm assembly 1.

[0072] In this embodiment, the porosity of the second diaphragm 12 is relatively large, and the porosity of the first diaphragm 11 is relatively low. Thus, in the diaphragm assembly 1 , the size of the voids can form a gradient distribution, which is beneficial to improving the liquid retention capacity of the diaphragm assembly 1 .

[0073] Figure 5 This is a schematic diagram of a diaphragm assembly according to an embodiment of the present application. Figure 5 As shown, the second diaphragm 12 includes: a second base film 121 , and the second base film 121 is located on a side of the first coating layer 112 away from the first base film 111 .

[0074] As an example, the first base film 111 and the second base film 121 are made of the same material and have the same porosity. In addition, the first base film 111 and the second base film 121 can also be made of different materials and / or have different porosities, and the embodiments of the present application include but are not limited to this.

[0075] In this embodiment, the second diaphragm 12 only includes the second base film 121, and the first coating layer 112 is disposed between the first base film 111 and the second base film 121. The porosity of the second base film 121 is greater than the porosity of the first coating layer 112, and the size of the voids in the second base film 121 is greater than the size of the voids in the first coating layer 112, so that a gap with a gradient distribution can be formed between the second base film 121 and the first coating layer 112.

[0076] Figure 6 is a schematic diagram of a diaphragm assembly according to an embodiment of the present application, Figure 6 This is a schematic diagram of a diaphragm assembly according to an embodiment of the present application. Figure 6 As shown, the second diaphragm 12 includes: a second coating layer 122 , and the second coating layer 122 is located on a side of the first coating layer 112 away from the first base film 111 .

[0077] For example, Figure 6 As shown, the second diaphragm 12 includes a second base film 121 and a second coating 122, the first coating 112 is located between the first base film 111 and the second diaphragm 12, and the second base film 121 is located between the first coating 112 and the second coating 122. As an example, the porosity of the second base film 121 is greater than the porosity of the first coating 112, and the porosity of the second coating 122 is greater than the porosity of the first coating 112.

[0078] For example, Figure 7 As shown, the second diaphragm 12 includes a second base film 121 and a second coating 122, the first coating 112 is located between the first base film 111 and the second diaphragm 12, and the second coating 122 is located between the first coating 112 and the second base film 121. As an example, the porosity of the second base film 121 is greater than the porosity of the first coating 112, and the porosity of the second coating 122 is greater than the porosity of the first coating 112.

[0079] In this embodiment, the size of the gaps in the diaphragm assembly 1 can form a gradient distribution, which is beneficial to improving the liquid retention capacity of the diaphragm assembly 1.

[0080] exist Figures 4 to 6 In the structure of the diaphragm assembly 1 shown, the first diaphragm 11 and the second diaphragm 12 can be prepared separately, and then the first diaphragm 11 and the second diaphragm 12 are combined together. Among them, the second diaphragm 12 can be a diaphragm in the related art, which facilitates the preparation of the diaphragm assembly 1 and reduces the complexity of the preparation of the diaphragm assembly 1.

[0081] In some embodiments, the second diaphragm 12 only includes the second coating 122, and the first coating 112 is located between the first base film 111 and the second coating 122. The second coating 122 can be prepared by spraying, coating, or the like on the surface of the first coating 112.

[0082] In some embodiments, at a length of 200 nm, the number A of voids on the surface of the first coating 112 satisfies: 3≤A≤8.

[0083] The gaps can be the outlet or inlet for ion transmission. Along the thickness direction of the diaphragm assembly 1, multiple interconnected gaps can form channels for ion transmission. The channels are used to transmit metal ions, such as sodium ions; sodium ions can be transmitted from the positive electrode sheet to the negative electrode sheet through the channels in the diaphragm assembly 1. For example, Figure 2 As shown, the channel may refer to the solid line with black double arrows in the figure, which indicates that metal ions can pass through the diaphragm assembly 1 through the channel; the gap may refer to the minimum unit 1120 of the first coating 112 and the gap between the minimum units 1120.

[0084] The number of voids on the surface of the first coating layer 112 refers to the number of voids on one side of the surface in the thickness direction of the first coating layer 112 , where the surface is perpendicular to the thickness direction of the diaphragm assembly 1 .

[0085] At a length of 200 nm, the number A of voids can be 3, 4, 5, 6, 7, 8 or any value within the above range. Compared to a diaphragm assembly having a number of voids less than 3 at a length of 200 nm, the first coating 112 has more voids, so that the size of the voids is smaller, dendrites are not easy to pass through the voids, the diaphragm assembly 1 is denser, the risk of being punctured by dendrites is reduced, and the risk of short circuit in the battery cell is reduced. In addition, the diaphragm assembly 1 is denser, and the requirements for the thickness of the diaphragm assembly 1 are correspondingly reduced. The diaphragm assembly 1 can achieve the effect of preventing dendrites from piercing the diaphragm assembly 1 when the thickness remains unchanged or even decreases, thereby reducing the risk of the thickness of the diaphragm assembly 1 increasing and causing adverse effects on the performance of the battery cell.

[0086] At a length of 200 nm, the number of gaps A can be referred to as, Figure 1 The number of gaps that a length of 200 nm passes through in the x-direction.

[0087] When the thickness of the diaphragm assembly 1 does not increase or even decreases, although the size of the gap is small, it may cause the ion transmission path to be tortuous; but because the thickness of the diaphragm assembly 1 does not increase or even decreases, the impact on the ion transmission path is small, and thus the performance of the battery cell such as the rate will not be deteriorated.

[0088] As an example, a scanning electron microscope (SEM) can be used to photograph the surface of the diaphragm assembly 1 to obtain an SEM image, and then a ruler can be used to draw lines to count the number of voids in the image. In particular, statistics can be performed on multiple areas, and the median obtained by the statistics is taken as the number of voids.

[0089] In some embodiments, at a length of 200 nm, the number A of surface voids of the first coating 112 satisfies: 3≤A≤6. For example, A is 3, 4, 5, 6, or an average value within the above range.

[0090] In some embodiments, the number B of voids on the surface of the first coating 112 in an area of ​​200 nm×200 nm satisfies: 10≤B≤60.

[0091] For example, B is 10, 20, 35, 50, 60 or any value within the above range. The statistics of the value of B can be performed with reference to the statistics of the value of A. As an example, multiple areas of 200 nm×200 nm are taken, multiple numbers of gaps in the multiple areas are counted, and the median of the multiple numbers is taken as B.

[0092] In this embodiment, by setting B to meet the above range, the diaphragm assembly 1 is denser and the strength against dendrite penetration is increased; at the same time, the thickness requirement of the diaphragm assembly 1 can be reduced to compensate for other adverse effects that may be caused by the reduction in the size of the voids; in addition, the number of voids will not be too many, so the particle size of the inorganic material will not be too small, which can reduce the risk of gelation of the slurry of the first coating 112 during the preparation of the slurry of the first coating 112.

[0093] The value of A and / or B is related to the volume median particle size Dv50 of the inorganic material. Generally speaking, the smaller the volume median particle size Dv50 of the inorganic material is, the larger the value of A and / or B is. When the volume median particle size Dv50 of the inorganic material is 0.04 μm to 0.16 μm, A is generally 3 to 8, and B is generally 10 to 80 or 10 to 60.

[0094] Therefore, by setting A and / or B to meet the above range, the diaphragm assembly 1 of the embodiment of the present application is beneficial to reducing the risk of short circuit of the battery cell, and is also beneficial to taking into account the rate performance of the battery cell, so that the battery cell can have better comprehensive performance.

[0095] In some embodiments, in the first coating layer 112, the size C of the gaps between the inorganic materials satisfies: C≤50nm; optionally, C≤20nm. In this way, the first coating layer 112 is relatively dense, and the risk of the diaphragm assembly 1 being punctured is relatively low.

[0096] C can be 50 nm, 30 nm, 20 nm, 10 nm or any value within the above range. The gap can be treated as an inscribed circle, and the radius of the inscribed circle is the size of the gap.

[0097] The size of the gaps between the inorganic materials can be achieved by setting the particle size of the inorganic material particles. Generally speaking, the smaller the particle size of the inorganic material particles (such as the volume median particle size Dv50), the smaller the size of the gaps. When the volume median particle size Dv50 of the inorganic material is between 0.04 μm and 0.16 μm, C is generally between 10 nm and 50 nm. The smaller the size of the gaps between the inorganic materials, the denser the first coating 112, the stronger the ability to resist dendrite puncture, and the lower the risk of short circuit in the battery cell.

[0098] In some embodiments, the inorganic material includes a ceramic material; optionally, the inorganic material includes at least one of silicon dioxide, aluminum oxide, zirconium oxide or boehmite. The above inorganic materials are used to facilitate the preparation of a relatively dense first coating 112.

[0099] As an example, the inorganic material includes aluminum oxide. For example, the inorganic material of the surface of the first coating 112 close to the negative electrode plate is aluminum oxide, and the inorganic material at other positions can be aluminum oxide or boehmite, etc. This is conducive to reducing the impact of hydroxyl groups in boehmite on the negative electrode plate.

[0100] In some embodiments, the surface density D of the first coating 112 satisfies: D≤3 g / mm 2 ; Optionally, D≤2.5g / mm 2 Thus, the first coating layer 112 has a smaller surface density, and thus the first coating layer 112 has a smaller thickness.

[0101] The surface density of the first coating layer 112 is related to the coating amount of the slurry during the preparation of the first coating layer 112. Under the same coating weight, since the particle size of the inorganic material in the embodiment of the present application is smaller, the first coating layer 112 is denser, and the surface density of the first coating layer 112 is larger, so that the thickness of the prepared first coating layer 112 is smaller, so that the first coating layer 112 can have a smaller thickness and a greater degree of density, and has a greater number of voids per unit length or area.

[0102] In some embodiments, the thickness d1 of the first coating layer 112 satisfies: 1.5 μm≤d1≤4 μm; alternatively, d1 satisfies: 1.5 μm≤d1≤2 μm.

[0103] d1 refers to the total thickness of the first coating layer 112 in the first diaphragm 11. As an example, when the first coating layer 112 is disposed on only one surface of the first base film 111, d1 refers to the thickness of one layer of the first coating layer 112. As another example, when the first coating layer 112 is disposed on both surfaces of the first base film 111, d1 refers to the sum of the thicknesses of the two layers of the first coating layer 112.

[0104] d1 may be 1.5 μm, 2 μm, 3 μm, 4 μm or any value within the above range. d1 may be an average thickness of the first coating 112 , for example, an average value of a maximum thickness and a minimum thickness.

[0105] The smaller the value of d1 is, the more conducive it is to reducing the transmission path of ions, thereby helping to improve the rate performance of the battery cell; in addition, it is also beneficial to improving the energy density of the battery cell.

[0106] In this way, the first coating 112 has a smaller thickness and a higher degree of densification, so that the diaphragm assembly 1 has a suitable tortuosity, the metal ions have a transmission path of suitable length, and the battery cell can have a higher rate performance with a lower short circuit risk.

[0107] In the embodiment of the present application, with the same coating weight, the thickness of the first coating 112 can be reduced by 5-25% by setting the particle size of the inorganic material, so that the setting of the diaphragm assembly in the embodiment of the present application is also beneficial to improving the energy density of the battery.

[0108] In some embodiments, the relationship between the volume average particle size Dv50 of the inorganic material and the thickness d1 of the first coating 112 satisfies: Dv50 / d1≤0.08; optionally, 0.02≤Dv50 / d1≤0.08. In this way, the thickness of the first coating 112 is small, and the particle size of the inorganic material of the first coating 112 is small, so that the diaphragm assembly 1 can have a higher density and a shorter ion transmission path.

[0109] In some embodiments, the porosity σ0 of the diaphragm assembly 1 satisfies: 30%≤σ0≤40%. In this way, the porosity of the diaphragm assembly 1 is lower, the diaphragm assembly 1 is denser, and the risk of being punctured by dendrites is lower, so the risk of short circuit of the battery cell is lower.

[0110] The porosity σ0 of the diaphragm assembly 1 can be 30%, 35%, 40% or any value within the above range. Compared with the diaphragm assembly with a porosity greater than 40%, the porosity of the diaphragm assembly 1 of this embodiment is lower, so the diaphragm assembly 1 is denser and has a lower risk of being punctured by dendrites, which can better protect and reduce the risk of short circuit of the battery cell.

[0111] In some embodiments, the porosity of the diaphragm assembly 1 may also be greater than 40%, for example, 45%. Compared with the diaphragm assembly of the related art, even if the porosity of the diaphragm assembly 1 is the same, the volume average particle size of the inorganic material of the first coating 112 of the diaphragm assembly 1 of the embodiment of the present application is smaller, and the surface of the first coating 112 has more voids per unit length or area, and the size of the voids is smaller, so the diaphragm assembly of the embodiment of the present application has a better protection effect on dendrites.

[0112] In some embodiments, when the diaphragm assembly 1 only includes the first diaphragm 11, when the porosity of the first base film 111 is 30% and the volume average particle size of the inorganic material in the first coating 112 is 0.04μm to 0.16μm, the porosity of the diaphragm assembly 1 can be around 30% to 35%; when the diaphragm assembly 1 also includes the second diaphragm 12, the porosity of the diaphragm assembly 1 can be around 35% to 36%.

[0113] In some embodiments, when the diaphragm assembly 1 only includes the first diaphragm 11, when the porosity of the first base film 111 is greater than 30% (for example, 40% to 50%), and the volume average particle size of the inorganic material in the first coating 112 is 0.04 μm to 0.16 μm, the porosity of the diaphragm assembly 1 can be around 40% to 45%.

[0114] In some embodiments, the first base film 111 and / or the second base film 121 includes at least one of a polyethylene film (PE film), a polypropylene film (PP film), or a composite film formed of a polyethylene film and a polypropylene film.

[0115] The first base film 111 and / or the second base film 121 may be a single-layer film or a composite film.

[0116] The composite film formed of polyethylene and polypropylene may be a multilayer film formed of PE film and PP film, such as PE film / PP film, PE film / PP film / PE film, etc. When the first base film 111 and / or the second base film 121 is a multilayer film, the materials of each layer may be the same or different.

[0117] The material of the first base film 111 and / or the second base film 121 may also include at least one of glass fiber, non-woven fabric or polyvinylidene fluoride.

[0118] [Positive electrode]

[0119] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on the positive electrode current collector.

[0120] The positive electrode current collector may be a metal foil or a composite current collector. For example, the positive electrode current collector may be an aluminum foil.

[0121] The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0122] The positive electrode film layer includes a positive electrode active material. The positive electrode active material can be a positive electrode active material for a battery known in the art. For example, in a lithium metal battery or a lithium ion battery, the positive electrode active material is lithium iron phosphate, a ternary material, a lithium-rich manganese-based material, etc.; in a sodium metal battery or a sodium ion battery, the positive electrode active material is a Prussian blue analog, a sodium-containing phosphate, a sodium-containing transition metal oxide, etc.

[0123] The positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0124] The positive electrode film layer may also optionally include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0125] [Negative electrode]

[0126] The negative electrode plate includes a negative electrode current collector. The negative electrode current collector may be a metal foil or a composite current collector. The negative electrode current collector may be a copper foil. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0127] [Electrolytes]

[0128] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application embodiment has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0129] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent. The electrolyte salt may be a sodium salt, a lithium salt, etc. depending on the type of the battery monomer.

[0130] The lithium salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0131] Sodium salts may include NaPF6, NaBF4, NaN(SO2F)2, NaClO4, and the like.

[0132] The solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0133] The electrolyte may also optionally include negative electrode film-forming additives, positive electrode film-forming additives, and may also include performance additives that can improve certain battery properties, such as improving battery overcharge performance, improving battery high temperature or low temperature performance, etc.

[0134] [Battery Cell]

[0135] An embodiment of the present application provides a battery cell, comprising the diaphragm assembly 1 in the above embodiment.

[0136] The embodiment of the present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. The battery cell may be an ion battery cell, a metal battery cell or the like.

[0137] Metal battery cells can also be called "negative electrode-free" battery cells. In the battery cell, the active metal ions are initially stored in the positive electrode active material. During the initial charging process, the metal ions move from the positive electrode to the negative electrode and deposit on the negative electrode current collector to form metal. Subsequently, during the discharge process, the metal ions detach from the negative electrode and embed into the positive electrode.

[0138] In a metal battery cell, the negative electrode may only include a negative electrode current collector, and does not include negative electrode active materials such as graphite. In some special settings, specific materials may also be provided on the surface of the negative electrode current collector to improve the conductivity and other properties of the negative electrode sheet.

[0139] In some embodiments, the battery cells are alkali metal battery cells; alternatively, the battery cells are sodium metal battery cells.

[0140] Since the problem of dendrites is more obvious in the process of charging and discharging of alkali metal battery cells, higher requirements are placed on the diaphragm assembly 1. In alkali metal battery cells, the use of the diaphragm assembly 1 of the embodiment of the present application can reduce the risk of dendrites piercing the diaphragm assembly 1, thereby reducing the risk of internal short circuits in the battery cells, and at the same time, the battery cells have better rate performance.

[0141] Alkali metal battery cells include lithium metal battery cells, sodium metal battery cells, potassium metal battery cells, zinc metal battery cells, and the like.

[0142] In some embodiments, the battery cell is a sodium ion battery cell, a zinc ion battery cell or a lithium ion battery cell. In the case of sodium precipitation in a sodium ion battery cell or lithium precipitation in a lithium ion battery cell, the diaphragm assembly 1 is relatively dense, so the risk of being punctured by the precipitated lithium dendrites or sodium dendrites is low. In addition, the sodium ion battery cell, the zinc ion battery cell or the lithium ion battery cell can also be a battery cell with a smaller CB value.

[0143] The CB value may refer to the ratio of the negative electrode capacity to the positive electrode capacity on the opposite side. When the CB value is small, for example, less than 1, the probability of dendrites precipitating on the negative electrode plate increases. By adopting the diaphragm assembly 1 of the embodiment of the present application, the risk of dendrites piercing the diaphragm assembly 1 is low, thereby reducing the risk of short circuit of the battery cell.

[0144] In some embodiments, the battery cell further includes: a positive electrode sheet and a negative electrode sheet, the diaphragm assembly 1 is disposed between the positive electrode sheet and the negative electrode sheet, and the first coating 112 faces the negative electrode sheet. In this way, the negative electrode sheet faces the side of the diaphragm assembly 1 where the first coating 112 is disposed (for example, the first coating 112 is in direct contact with the negative electrode sheet), which is conducive to better protection of the diaphragm assembly 1.

[0145] Figure 8 Schematic diagram of a battery cell according to an embodiment of the present application. Figure 8 As shown, the battery cell 3 is a square battery cell and includes a housing 31 , an end cap assembly 32 and an electrode assembly 33 disposed in the housing 31 .

[0146] The electrode assembly 33 may be made of a positive electrode sheet, a negative electrode sheet and a separator assembly through a winding process or a lamination process.

[0147] The end cap assembly 32 includes an electrode terminal 322, such as Figure 8 As shown, the end cap assembly 32 includes two electrode terminals 322, one of which is a positive electrode terminal and the other is a negative electrode terminal.

[0148] The battery cell 3 further includes a current collecting member 34 for connecting the tab 331 of the electrode assembly 33 and the electrode terminal 322 .

[0149] In some embodiments, the battery cell is a secondary battery cell, which can be used multiple times by charging and discharging.

[0150] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more. The specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0151] [Battery]

[0152] An embodiment of the present application provides a battery, comprising the battery cell in the above embodiment. Fig. 9 Schematic diagram of a battery according to an embodiment of the present application. Fig. 9 As shown, the battery 5 may include a plurality of battery cells (not shown in the figure).

[0153] The battery cells 3 can directly form the battery 5 , or can first form a battery module, and then multiple battery modules form the battery 5 .

[0154] [Electrical devices]

[0155] An embodiment of the present application provides an electrical device, comprising the battery described in the above embodiment.

[0156] Fig.10 FIG. 1 is a schematic diagram of an electrical device according to an embodiment of the present application. Fig.10 As shown, the present application provides an electrical device 6, including the battery in the above embodiment.

[0157] Optionally, the electrical device may also be an energy storage device, a lighting device, a spacecraft, etc. The embodiments of the present application include but are not limited to these.

[0158] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0159] [Example]

[0160] Example 1

[0161] In Example 1, the structure of the diaphragm assembly 1 is shown in Figure 1 The diaphragm assembly 1 includes a first diaphragm 11 , and the first diaphragm 11 includes a first base film 111 and a first coating 112 located on both sides of the first base film 111 .

[0162] The thickness d2 of the first base film 111 is 12 μm, the thickness d1 of the first coating layer 112 is 2 μm, and the first coating layer 112 includes aluminum oxide, and the volume average particle size Dv50 of the aluminum oxide is 0.04 μm.

[0163] Embodiment 2-6

[0164] The difference between Example 2-6 and Example 1 is that the volume average particle size Dv50 of aluminum oxide in the first coating is different. In addition, the thickness of the first coating in Examples 2-6 is the same, but the surface density of the first coating is different due to the different volume average particle size Dv50 of aluminum oxide.

[0165] Examples 7-12

[0166] The difference between Examples 7-12 and Example 1 is that the surface density of the first coating layer is different.

[0167] In Examples 7 to 12, since the surface density of each example in Examples 7 to 12 is the same, but the volume average particle size Dv50 of aluminum oxide is different, the thickness of the first coating layer is different.

[0168] Examples 13-15

[0169] The difference between Examples 13-15 and Example 3 is that the surface density of the first coating layer is different, and the thickness d1 of the first coating layer is different.

[0170] Comparative Example 1

[0171] The difference between Comparative Example 1 and Example 1 is that the diaphragm only includes a base film but does not include a coating layer.

[0172] Comparative Example 2

[0173] The difference between Comparative Example 2 and Example 1 is that the volume average particle size of the inorganic material is larger.

[0174] Comparative Example 3

[0175] The difference between Comparative Example 3 and Example 1 is that the volume average particle size of the inorganic material is larger, and a second diaphragm is additionally provided, the thickness of the second diaphragm is about 14 μm, and the overall thickness of the diaphragm assembly is larger.

[0176] Table 1 Experimental parameters and results of embodiments and comparative examples

[0177]

[0178]

[0179] [Preparation of sodium metal battery monomers]

[0180] (1) Preparation of positive electrode sheet: The positive electrode active material NaFeP2O7, the conductive agent carbon black Super P, and the binder polyvinylidene fluoride (PVDF) are stirred and mixed in a solvent N-methylpyrrolidone (NMP) at a weight ratio of 96:2:2 to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and then dried and cold pressed to obtain a positive electrode sheet.

[0181] (2) Preparation of negative electrode sheet: A copper foil with a thickness of 6 μm was used as the negative electrode current collector.

[0182] (3) Isolation film: A polypropylene film is used as the first base film, and a corresponding coating material is disposed on the first base film to prepare a first coating. In the case where a second diaphragm is disposed, the first diaphragm and the second diaphragm are connected by gluing.

[0183] (4) Preparation of electrolyte: Sodium hexafluorophosphate with a concentration of 1 mol / L was dissolved in a mixed solvent of diethylene glycol dimethyl ether / tetraethylene glycol dimethyl ether in a volume ratio of 1:1 to obtain an electrolyte.

[0184] (5) Preparation of sodium metal battery cells: stack and wind the above-mentioned positive electrode plates, separators, and negative electrode plates in order to obtain an electrode assembly; place the electrode assembly in an outer package, add the above-prepared electrolyte, and obtain a sodium metal battery cell after packaging, standing, forming, aging and other processes.

[0185] [Porosity test]

[0186] (1) The porosity of the diaphragm assembly can be tested with reference to GB / T33052-2016. Cut the diaphragm assembly into a suitable size and measure the volume V of the diaphragm assembly; place the diaphragm assembly in a bottle containing hexadecane for a certain period of time so that the pores in the diaphragm are completely filled with hexadecane, and calculate the volume V2 of the absorbed hexadecane.

[0187] The porosity σ0 of the diaphragm assembly is = (V2 / V1) x 100%.

[0188] (2) The porosity of the base film can be measured in the following manner: take a base film of appropriate size (it can refer to either the first base film or the second base film) to obtain the macroscopic size V3 (containing pores) of the base film; use the above method to measure the volume V4 of hexadecane absorbed by the base film, and the porosity of the base film is σ1 = (V4 / V3) × 100%.

[0189] (3) The porosity of the coating can be obtained by:

[0190] The porosity of the first coating is the difference between the porosity of the first diaphragm and the porosity of the first base film; the porosity of the second coating is the difference between the porosity of the second diaphragm and the porosity of the second base film. Wherein, in the case where the diaphragm assembly only includes the first diaphragm, the porosity of the first diaphragm is the porosity of the diaphragm assembly; in the case where the diaphragm assembly includes the first diaphragm and the second diaphragm, the first diaphragm can be separated from the second diaphragm, so that the porosities of the first diaphragm and the second diaphragm can be measured respectively according to the method in (1).

[0191] [Test of diaphragm assembly thickness]

[0192] The diaphragm assembly is processed by ion polishing technology (also known as ion grinding) to obtain the diaphragm cross section, and then a scanning electron microscope (SEM) is used to test the thickness of the base film and the thickness of the coating.

[0193] [Measurement of gap size]

[0194] The diaphragm assembly was observed using a scanning electron microscope (SEM), and the size of the gap was measured at a magnification of 3000kx with reference to a 200nm ruler. The gap can be treated as an inscribed circle, and the radius of the inscribed circle is the size of the gap.

[0195] [Measurement of the number of gaps]

[0196] The surface of the diaphragm assembly is photographed using a scanning electron microscope (SEM) to obtain an SEM image, and then a ruler is used to draw lines, take a specific length or a specific area, and count the number of voids in the image. In this case, statistics can be performed on multiple areas, and the median obtained by the statistics is taken as the number of voids.

[0197] [Internal short circuit test]

[0198] In the embodiment of the present application, whether an internal short circuit occurs in a battery cell can be reflected by the voltage drop rate of the battery cell.

[0199] The battery cell is charged at 0.33C to U1 (wherein U1 is set according to the positive electrode material in the battery cell, and for the sodium metal battery in the embodiment of the present application, U1 is 3.65V); it is left to stand for 2 days to obtain an open circuit voltage U2; then it is left to stand for another day to obtain an open circuit voltage U3, and the voltage drop rate is calculated to be (U2-U3) / 24h; if the voltage drop rate is greater than the threshold value of 0.4mV / h, it is considered that an internal short circuit occurs in the battery cell.

[0200] [Rate performance test]

[0201] The rate performance is reflected by the capacity retention rate at 2C rate, and the capacity retention rate at 2C rate = C1 / C0.

[0202] C0 test: The prepared battery cell was left to stand for 30 minutes, then charged to 3.65V at a constant current of 0.33C at 25°C, and then left to stand for 30 minutes. Then, it was discharged to 1.5V at a constant current of 0.33C and left to stand for 10 minutes. The capacity obtained by this test method is recorded as C0.

[0203] C1 test: The prepared battery cell was left to stand for 30 minutes, then charged to 3.65V at 2C0 constant current at 25°C, and then left to stand for 30 minutes. Then, it was discharged to 1.5V at 0.33C constant current and left to stand for 10 minutes. The capacity obtained by this test method is recorded as C1.

[0204] In this test method, the rate performance can also reflect the risk of internal short circuit of the battery cell to a certain extent. For example, if the battery cell has an internal short circuit, self-discharge may occur inside the battery cell, thereby reducing the theoretical capacity that can be discharged by the battery cell, and the corresponding rate performance will also be poor.

[0205] In Comparative Example 1, the diaphragm assembly is only provided with a base film, and the battery cell prepared by the diaphragm assembly has an internal short circuit, and the voltage drop rate is very large. In Comparative Example 2, the volume average particle size of the inorganic material of the first coating layer in the diaphragm assembly is large, which results in the diaphragm assembly being not dense enough, the battery cell having an internal short circuit, and the voltage drop rate being large.

[0206] In Comparative Example 3, the volume average particle size of the inorganic material of the first coating layer in the diaphragm assembly is larger, and a second diaphragm is provided in the diaphragm assembly, so that the overall thickness of the diaphragm assembly is thicker. Although the voltage drop rate of the battery cell is reduced and the battery cell does not have an obvious internal short circuit, the rate performance of the battery cell is greatly reduced.

[0207] As shown in Examples 1-15 and Comparative Examples 1-3, the battery cells including the diaphragm assemblies of the embodiments of the present application did not have internal short circuits and had high rate performance, which can reflect that the diaphragm assemblies of the embodiments of the present application have good resistance to dendrite puncture and have a suitable ion transmission path.

[0208] As shown in Examples 1-5, when the thickness of the first coating layer is the same, the smaller the particle size of the inorganic material, the denser the first coating layer, and the greater the surface density of the first coating layer; and when the volume average particle size of the inorganic material is in the range of 0.04 μm to 0.16 μm, the battery cell will not have an internal short circuit, and the battery cell has a higher rate performance. As shown in Example 3, when the volume average particle size of the inorganic material is 0.1 μm, the battery cell exhibits a higher rate performance.

[0209] As shown in Examples 7-11, when the first coating has the same surface density, as the particle size of the inorganic material decreases, the thickness of the first coating decreases, the capacity retention rate of the battery cell at a 2C rate basically shows an increasing trend, and the rate performance is improved. As shown in Example 9, when the volume average particle size of the inorganic material is 0.1 μm, the battery cell exhibits a higher rate performance.

[0210] As shown in Examples 6 and 12, when the Dv50 of the inorganic material is 0.02 μm (less than 0.04 μm), the particle size of the inorganic material is relatively small. Although the first coating is relatively dense, due to the small particle size of the inorganic material, the risk of gelation of the slurry increases during the preparation process; at the same time, the rate performance of the battery cell is also reduced.

[0211] As shown in Examples 3, 9 and Examples 13-15, as the thickness of the first coating layer increases, the strength of the first coating layer against dendrite penetration increases, but the ion transmission path becomes longer and the rate performance of the battery cell decreases.

[0212] In combination with Examples 13-15 and 1-12, the surface density of the first coating is set to be less than or equal to 3 g / mm 2 It is beneficial to improve the rate performance of the battery cell; further, the surface density of the first coating is set to be less than 2.5g / mm 2 , which is conducive to further improving the rate performance of battery cells.

[0213] As shown in Examples 1-15, by setting the thickness of the first coating to 1.5 μm to 4 μm, the battery cell can have a higher rate performance without short circuiting; further, by setting the thickness of the first coating to 1.5 μm to 2 μm, the battery cell can have an even higher rate performance.

[0214] Compared to lithium metal batteries, in sodium metal batteries, in general, the growth of dendrites is more obvious. In addition, compared to ion batteries, the growth of dendrites in metal batteries is also more obvious. Therefore, the diaphragm assembly of the embodiment of the present application can also be applied to lithium metal batteries, sodium ion batteries and lithium ion batteries. In addition, the diaphragm assembly of the embodiment of the present application can also be applied to other alkali metal batteries or ion batteries.

[0215] In addition, in the present application, some other embodiments are provided. In some embodiments, an embodiment with a different porosity of the first base film 111 from that of embodiment 1 is provided; the test results show that the porosity of the first base film in embodiment 3 is smaller, the surface of the first coating is smoother, and it is less likely to produce dendrites; and in the embodiment with a larger porosity of the first base film, dendrites are more likely to be produced compared to embodiment 3; wherein, whether dendrites are produced or how many dendrites are produced can be determined by disassembling the battery and observing the metal dendrites on the surface of the diaphragm assembly or the electrode. In some embodiments, diaphragm assemblies of different structures are tested; the test results show that the first coating is provided only on one side of the first base film, and the battery cell prepared by the diaphragm assembly has a lower voltage drop rate (no short circuit) and a higher rate performance; the second diaphragm is provided, the overall porosity of the diaphragm assembly becomes larger, and the diaphragm assembly has a better liquid retention capacity.

[0216] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A diaphragm assembly, characterized in that: include: The first diaphragm, The first diaphragm includes a first base film and a first coating layer, the first coating layer is located on the surface of at least one side of the first base film, the first coating layer includes an inorganic material, and the volume average particle size Dv50 of the inorganic material satisfies: Dv50≤0.16μm.

2. The diaphragm assembly according to claim 1, characterized in that: The volume average particle size Dv50 of the inorganic material satisfies: 0.04 μm≤Dv50≤0.16 μm.

3. The diaphragm assembly according to claim 1 or 2, characterized in that: The porosity σ1 of the first base film satisfies: 30%≤σ1≤45%.

4. The diaphragm assembly according to any one of claims 1 to 3, characterized in that: The diaphragm assembly further comprises: A second diaphragm is located on a side of the first coating layer away from the first base film, and the porosity of the second diaphragm is greater than the porosity of the first diaphragm.

5. The diaphragm assembly according to claim 4, characterized in that: The second diaphragm comprises: A second base film, wherein the second base film is located on a side of the first coating layer away from the first base film.

6. The diaphragm assembly according to claim 4, characterized in that The second diaphragm comprises: a second base film and a second coating, wherein the second coating is located between the second base film and the first coating; or The second base film is located between the second coating layer and the first coating layer.

7. The diaphragm assembly according to any one of claims 1 to 6, characterized in that: In an area of ​​200 nm×200 nm, the number B of voids on the surface of the first coating layer satisfies: 10≤B≤60.

8. The diaphragm assembly according to any one of claims 1 to 7, characterized in that: In the first coating layer, a size C of the gaps between the inorganic materials satisfies: C≤50nm; optionally, C≤20nm.

9. The diaphragm assembly according to any one of claims 1 to 8, characterized in that: The inorganic material includes a ceramic material; optionally, the inorganic material includes at least one of silicon dioxide, aluminum oxide, zirconium oxide or boehmite.

10. The diaphragm assembly according to any one of claims 1 to 9, characterized in that: The surface density D of the first coating satisfies: D≤3g / mm 2 ; Optionally, D≤2.5g / mm 2 .

11. The diaphragm assembly according to any one of claims 1 to 10, characterized in that: The thickness d1 of the first coating satisfies: 1.5 μm≤d1≤4 μm; optionally, d1 satisfies: 1.5 μm≤d1≤2 μm.

12. The diaphragm assembly according to any one of claims 1 to 11, characterized in that: The porosity σ0 of the diaphragm assembly satisfies: 30%≤σ0≤40%.

13. A battery cell, characterized in that: The invention comprises the diaphragm assembly according to any one of claims 1 to 12.

14. The battery cell according to claim 13, characterized in that: The battery cell further includes: a positive electrode sheet and a negative electrode sheet, the diaphragm assembly is disposed between the positive electrode sheet and the negative electrode sheet, and the first coating faces the negative electrode sheet.

15. The battery cell according to claim 13 or 14, characterized in that: The battery cell is an alkali metal battery cell; optionally, the battery cell is a sodium metal battery cell.

16. A battery, characterized in that: The invention comprises a battery cell as claimed in any one of claims 13 to 15.

17. An electrical device, characterized in that: Comprising the battery of claim 16.

Citation Information

Patent Citations

  • Isolating membrane and electrochemical device

    CN109980164A

  • Separator for electrochemical device and method for manufacturing same

    CN116134671A

  • Separator, electrochemical device, and electronic apparatus

    CN116315459A

  • Coating composition for battery diaphragm, composite diaphragm and secondary battery

    CN116454540A

  • Rechargeable lithium battery

    JP2015037078A

Cited By

  • Separator assembly, battery cell, battery and electric device

    EP4787596A1